2016
DOI: 10.5194/amt-9-5265-2016
|View full text |Cite
|
Sign up to set email alerts
|

A versatile, refrigerant- and cryogen-free cryofocusing–thermodesorption unit for preconcentration of traces gases in air

Abstract: We present a compact and versatile cryofocusingthermodesorption unit, which we developed for quantitative analysis of halogenated trace gases in ambient air. Possible applications include aircraft-based in situ measurements, in situ monitoring and laboratory operation for the analysis of flask samples. Analytes are trapped on adsorptive material cooled by a Stirling cooler to low temperatures (e.g. −80 • C) and subsequently desorbed by rapid heating of the adsorptive material (e.g. +200 • C). The set-up involv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…An electron capture detector (ECD) is used in an isothermal channel in a similar set-up as used during the SPURT campaign (Bönisch et al, 2009(Bönisch et al, , 2008Engel et al, 2006) to measure SF 6 and CFC-12 with a time resolution of 1 min. The second channel is temperature programmed and uses a cryogenic pre-concentration system (Obersteiner et al, 2016;Sala et al, 2014) and a mass spectrometer (MS) for detection. It is similar to the set-up described by Sala et al (2014) and measures halocarbons in the chemical ionization mode (e.g.…”
Section: Instrumentation and Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…An electron capture detector (ECD) is used in an isothermal channel in a similar set-up as used during the SPURT campaign (Bönisch et al, 2009(Bönisch et al, , 2008Engel et al, 2006) to measure SF 6 and CFC-12 with a time resolution of 1 min. The second channel is temperature programmed and uses a cryogenic pre-concentration system (Obersteiner et al, 2016;Sala et al, 2014) and a mass spectrometer (MS) for detection. It is similar to the set-up described by Sala et al (2014) and measures halocarbons in the chemical ionization mode (e.g.…”
Section: Instrumentation and Observationsmentioning
confidence: 99%
“…Therefore, brominated VSLS are particularly effective with respect to ozone chemistry in the lower and lowermost stratosphere, below about 20 km, with the associated ozone decreases exerting a significant radiative effect . It has been shown that observed and modelled ozone show a better agreement if bromine from shortlived species is included in models (Sinnhuber and Meul, 2015;Fernandez et al, 2017;Oman et al, 2016). In particular for the Antarctic ozone hole, an enhancement in size by 40 % and an enhancement in mass deficit by 75 % was simulated due to VSLS (Fernandez et al, 2017) in comparison with a model run without VSLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The halocarbon measurements are based on adsorption-desorption gas chromatography / mass spectrometry (GC/MS). As halocarbon mixing ratios in the atmosphere are in the ppt range, pre-concentration of the sample air prior to gas chromatographic separation and detection is required (Obersteiner et al, 2016). In addition, the sample air is dried by passing over a 10 heated (80 • C) tube filled with magnesium perchlorate Mg(ClO 4 ) 2 .…”
Section: Halocarbon Measurementsmentioning
confidence: 99%
“…experimental setup was described in more details byHoker et al (2015) andObersteiner et al (2016).HIRES samples are measured relative to a laboratory standard which has been collected cryogenically at Jungfraujoch(Switzerland) in December 2007 and has been calibrated against standards of the Advanced Global Atmospheric Gases Experiment (AGAGE) in December 2018. Mixing ratios are reported in ppt on Scripps Institution of Oceanography (SIO) scales.…”
mentioning
confidence: 99%